Lentiviral vectors for inducible, transactivator-free advanced therapy medicinal products: Application to CAR-T cells - María Tristán-Manzano; Noelia Maldonado-Pérez; Pedro Justicia-Lirio; Marina Cortijo-Gutierréz; Pablo Tristán-Ramos; Carlos Blanco-Benítez; Kristina Pavlovic; Araceli Aguilar-González; Pilar Muñoz; Francisco J. Molina-Estevez; Valerie Griesche; Juan Antonio Marchal; et al. (Elsevier, 2023)
Controlling transgene expression through an externally administered inductor is envisioned as a potent strategy to improve safety and efficacy of gene therapy approaches. Generally, inducible ON systems require a chimeric transcription factor (transactivator) that becomes activated by an inductor, which is not optimal for clinical translation due to their toxicity. We generated previously the first all-in-one, transactivator-free, doxycycline (Dox)-responsive (Lent-On-Plus or LOP) lentiviral vectors (LVs) able to control transgene expression in human stem cells. Here, we have generated new versions of the LOP LVs and have analyzed their applicability for the generation of inducible advanced therapy medicinal products (ATMPs) with special focus on primary human T cells. We have shown that, contrary to all other cell types analyzed, an Is2 insulator must be inserted into the 3' long terminal repeat of the LOP LVs in order to control transgene expression in human primary T cells. Importantly, inducible primary T cells generated by the LOPIs2 LVs are responsive to ultralow doses of Dox and have no changes in phenotype or function compared with untransduced T cells. We validated the LOPIs2 system by generating inducible CAR-T cells that selectively kill CD19+ cells in the presence of Dox. In summary, we describe here the first transactivator-free, all-one-one system capable of generating Dox-inducible ATMPs.